FISHERY AND POPULATION DYNAMICS OF A PRIZED MAJOR CARP LABEO ROHITA (HAMILTON, 1822) FROM THE MIDDLE STRETCHES OF THE RIVER GANGA, INDIA - RAY, ARCHISMAN; BHAKTA, DIBAKAR; DAS, BASANTA KUMAR; JOHNSON, CANCIYAL; RAMTEKE, MITESH; TIWARI, NITISH KUMAR; DASGUPTA, SUBHADEEP (Journal of the Inland Fisheries Society of India, 2025)
In the current study, the fishery and population dynamics of a prized Gangetic carp, Labeo rohita (Hamilton, 1822), were evaluated using length-frequency data collected monthly from the middle stretches of the Ganga River from April 2017 to December 2019. Using the FiSAT-II software package (FAO-ICLARM Stock Assessment Tools), population parameters were evaluated and computed for the collected data, which were grouped into 60-mm class intervals. Total mortality (Z), natural mortality (M), and fishing mortality (F) coefficients were calculated to be 1.28, 0.54, and 0.74, respectively. Using the length-converted catch curve approach, the estimated value of the exploitation ratio (E) was determined to be 0.58, somewhat higher than the ideal value (0.50). L. rohita has two unique recruitment seasons each year, one minor from February to March and the other significant from August to October, according to the Ganga River recruitment pattern. Findings from the current study indicated that L. rohita in the middle stretches of the Ganga are overfished. Fish stocks can be revived through management practices such as reducing fishing pressure by capping the number of boats or fishing hours, managing mesh size to prevent overfishing of both recruitment and growth, and establishing breeding places and closed seasons. To manage the L. rohita fisheries in the Ganga River systems effectively, research is also advised to understand the life-history traits of the species.